Upaya Kepala Sekolah dalam Meningkatkan Profesionalisme Guru di MTS Nahdlatul Wathon Kacamatan Licin - Afrida Nur Laili (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This study aims to determine the efforts of school principals in increasing teacher professionalism at MTS Nahdlatul Wathon, Licin District. The method used in this research is a qualitative method with a descriptive approach. There are three data collection techniques used, namely observation, interviews and documentation. Data analysis used in this research is interactive analysis. The results of the study show that school principals encourage teachers to participate in teacher working groups (KKG), increase teacher commitment through subject teacher deliberations (MGMP), involve teachers in training activities, training, seminars, workshops, upgrading, workshops and certification exams Teacher. In addition, the principal's efforts to increase teacher professionalism are trying to meet the needs for facilities and infrastructure, although they are still far from perfect, fostering good relationships with teachers, education staff, students and parents. Meanwhile, the inhibiting factors in the principal's efforts to increase teacher professionalism at MTS Nahdlatul Wathon, Licin District include, namely, when teachers are ordered to take part in activities, they sometimes make excuses and alternate throwing assignments.